Ratio to Return On Assets in Banking Subsector Companies Listed on the Indonesia Stock Exchange in 2016-2019 - Jauhari, Hendra; Devananta, Kenfi; Lais, Owen August; Gabriella, Gabriella; Januardin, Januardin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the effect of Cash Ratio, Capital Adequacy Ratio and Loan to Deposit Ratio on Return On Assets in banking sub-sector companies listed on the Indonesian stock exchange in 2016-2019. This research uses quantitative research methods to find the relationship between numerical data or numbers. . The data analysis model used during this research process is the multiple linear regression analysis model using the SPSS application ((Statistical Product and Service Solutions) version 24. During the 4-year period, namely; 2016-2019, there were 18 companies that met the criteria in the study. and produced 72 data samples.The results obtained are (1) It is known that the t-count Cash Ratio: 5.956 > t-table 1.996, so it can be concluded that there is an effect of X1 (Cash Ratio) on Y (ROA) (2) The t-value is known. Calculate Cash Adequacy Ratio: 3.300 > t table 1.996, so it can be concluded that there is an effect of X2 (Cash Adequacy Ratio) on Y (ROA). that there is no effect of X3 (Loan to Deposit Ratio) on Y (ROA) (4) Cash Ratio, Cash Adequacy Ratio, Loan to Deposit Ratio have a simultaneous effect on Return On Assets in Peru Banking sub-sector companies listed on the IDX for the 2016-2019 period. This is evidenced by the significance value of 0.00 indicating a value that is smaller than the predetermined significance value of 0.05.